(Re)descobrir o Museu Archeológico do Algarve de Estácio da Veiga - Filipe, Ana Margarida Vinagre (2018)
By the end of the 19th century, several museological institutions were created in Portugal. Each of them had its own role, more or less relevant, on the national museology’s history. One example that, despite existing for a small period of time, revealed itself as a landmark, was Museu Archeologico do Algarve (1880-1881). Resulting from the work of a single man, the archaeologist Estácio da Veiga (1828-1891), it is the first museum where the scientific nature of archaeology is followed. This museum appears within the context of uncountable discoveries made by Estácio da Veiga along the district of Faro between 1877 and 1878. Having a cutting-edge spirit, he sees the museum as a living institution, whose purpose goes way beyond the mere exhibition of artefacts. Estácio da Veiga creates a museum whose purpose stands out from the national context of that time: investigation and teaching. Despite its short existence, this museum’s collection is nowadays an important part of the collections of Museu Nacional de Arqueologia. To overcome this gap, we propose to create an exhibition focused on Estácio da Veiga’s life and work, and the Museu Archeologico do Algarve in particular, looking forward to reflecting the founder’s visionary character. This proposal is based on the biographical and documentary investigation that was carried out, here presented as context. Starting from the obtained results, it is possible to create an exhibition narrative that brings Estácio da Veiga’s ideas to the present, with an up-to-date reading. In this sense, we intend to elicit the interest from the public in the history of Portuguese museology and in the Museu Archeologico do Algarve